2017
DOI: 10.18034/mjmbr.v4i2.436
|View full text |Cite
|
Sign up to set email alerts
|

Seed Rate and Sowing Method Effects on Seed Quality of Bread Wheat (triticum aestivum L.) Varieties in Horo District, Western Ethiopia

Abstract: Although wheat varieties were released with recommended seed rates, farmers usually apply their specific seed rates for various reasons. A study was conducted in Horo District to determine the effect of seeding rate and sowing methods on the seed quality of bread wheat using field and laboratory experiments, in the 2011 cropping season. The field experiment was conducted at Shambu, Bako agricultural research center sub-site while the seed quality analysis was performed at seed laboratory of Holetta Agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…He also reported that seed with good size had more vigor and produced more shoot, root and coleoptile length with excellent utilization of seed reserves. Similar results were reported by (Geleta, 2017) who also reported maximum seedling root length at seeding density of 125 kg ha -1 whereas the shortest root length was observed at 200 kg ha -1 planting density. These findings show a similar trend that an optimal increase in seed rate results in enhanced root length however, an excessive planting density can negatively affect root length.…”
Section: Root Lengthsupporting
confidence: 89%
See 3 more Smart Citations
“…He also reported that seed with good size had more vigor and produced more shoot, root and coleoptile length with excellent utilization of seed reserves. Similar results were reported by (Geleta, 2017) who also reported maximum seedling root length at seeding density of 125 kg ha -1 whereas the shortest root length was observed at 200 kg ha -1 planting density. These findings show a similar trend that an optimal increase in seed rate results in enhanced root length however, an excessive planting density can negatively affect root length.…”
Section: Root Lengthsupporting
confidence: 89%
“…Contrarily, planting density of 100 kg ha -1 (8.70 cm, 10.71 cm, 8.52 cm) revealed more shoot length than higher planting density of 140 kg ha -1 (8.70 cm, 8.20 cm, 9.53 cm) although lesser than 120 kg ha -1 altogether (Table 5). Parallel conclusions were found by (Geleta, 2017) who also reported greater shoot length at an optimum seed rate of 125 kg ha -1 while the minimum shoot length was revealed at higher seeding density of 200 kg ha -1 . This disparity among shoot length may be due to lesser plant population at lower seed rate with minimum competition for nutrients, space, and sunlight.…”
Section: Root Lengthsupporting
confidence: 77%
See 2 more Smart Citations
“…Different sowing densities can modify not only yield but also the physiological potential of the seeds produced. For the wheat crop, Geleta (2017) found that an increase in plant density negatively affected the physiological potential of the seeds produced, which exhibited reduction in speed of germination and an increase in the number of abnormal plants they developed.…”
Section: Introductionmentioning
confidence: 99%